Pathophysiological aspects of the oral cavity diseases in children against the background of gastroesophageal reflux disease - S. A. Schneider; A. Yu. Salekh (Kazimierz Wielki University, 2019)
Gastroesophageal reflux disease is one of the most common, potentially dangerous gastroenterological diseases and according to the Ministry of Health of Ukraine, diseases of the gastrointestinal tract occupy one of the first places in the structure of childhood somatic pathology and tend to increase. It should be noted that for the most part, clinical manifestations of the gastroduodenal disease, which include gastroesophageal reflux disease, in children who are not always able to characterize their condition, are nonspecific, and therefore are diagnosed untimely. It is known that gastroesophageal reflux disease is characterized by a variety of clinical manifestations, including extra-extravascular, among which dental are some of the most common. Taking into account the fact that the oral cavity is an integral part of the gastrointestinal tract, the presence of gastroesophageal reflux with gastric contents rudely disturbs the existing acid-base balance and the composition of the microbiocenosis of the oral cavity in children. In particular, 82.35% of pediatric patients who suffered from gastroesophageal reflux disease had erosion of the hard dental tissues. The authors conducted deep meta-analysis of the main pathogenetic mechanisms of oral manifestations of gastroesophageal reflux disease in children.